Optimization of the methodology for assessing the specific endurance of football players - Lavrichenko V.V. ,; Kalinina I.N. ,; Grigoryan M.R. ,; Deb M.M. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the physiological focus of the modified J. Bangsbo football sprint test, where the reliability of data on the development of anaerobic and aerobic energy supply mechanisms ensures the validity and reliability of the assessment of the special endurance of football players. Methods and structure of the study. In the improved version of the football sprint test developed by J. Bangsbo, the emphasis is on simulating competitive conditions. The lactate level in blood taken from a peripheral vein was determined by the sports team doctor using a compact Lactat Scout analyzer 3-5 minutes after the test was completed. The study involved young athletes from the Youth Sports School "Football Academy" of the Krasnodar Territory, as well as members of the youth teams of the Krasnodar Territory and Rostov Region. The selection of participants was carried out according to the following criteria: age compliance with passport data with an acceptable deviation of ±0.5 years (15.5-16.5 years for 16-year-olds; 16.5-17.5 years for 17-year-olds; 17.5-18.5 years for 18-year-olds) and at least 8 years of training experience. Results and conclusions. Based on the analysis of lactate concentration in blood taken from the peripheral area, the researchers claim that the adapted sprint test can serve as a tool for assessing the efficiency of both anaerobic and aerobic energy supply processes at maximum work intensity. This is evidenced by the relatively low lactate level recorded after the test task in participants of different age groups, which reflects the specific motor activity characteristic of football players during the game.